Sistem Pakar Rekomendasi PC Rakitan Berdasarkan Kebutuhan Pengguna Menggunakan Metode Certainty Factor - Muhammad Ramadien Rizky Darmawan; Hardiansyah (CV. Multi Kreasi Media, 2025)
An The rapid development of computer technology presents challenges for novice users in selecting custom PC components that fit their needs and budget. This study develops a web-based expert system using the Certainty Factor (CF) method to provide component recommendations. The knowledge base covers CPU, RAM, motherboard, GPU, and storage, implemented with PHP, HTML, CSS, JavaScript, and MySQL. Users input their requirements through a simple interface, and the system processes them with a CF-based inference engine to generate recommendations along with confidence levels. The results show that the system provides accurate, relevant, and efficient recommendations for various needs, making it a practical solution for custom PC component selection